Modification of Sunless Tanning Solution for UV Protection Purposes - Grady, Jamie L. (My University, 2020)
One of the largest aspects of the cosmetics industry is sunless tanning products which provide a tan without harmful UVA and UVB rays from the sun or sunless tanning booths. Unfortunately, these topical agents do not provide additional sun protection. In order to improve the sun protection factor of an existing commercial sunless tanning solution, titanium dioxide (TiO2) and ascorbic acid (vitamin C) were used since they are common additives of cosmetic products. To test this idea, a model protein system was used by depositing a film of a gelatin, composed of peptides and proteins, onto a transparent glass slide. This model mimics the Maillard reaction, a browning effect, that occurs in the proteins within human skin. To evaluate the slow color development of the Maillard reaction absorbance measurements were taken at different time intervals.